2021
DOI: 10.3390/molecules26113231
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Low-Diacylglycerol Cocoa Butter Equivalents by Hexane Fractionation of Palm Stearin and Shea Butter

Abstract: Herein, we prepared 1,3-dipalmitoyl-2-oleoyl glycerol (POP)-rich fats with reduced levels of diacylglycerols (DAGs), adversely affecting the tempering of chocolate, via two-step hexane fractionation of palm stearin. DAG content in the as-prepared fats was lower than that in POP-rich fats obtained by previously reported conventional two-step acetone fractionation. Cocoa butter equivalents (CBEs) were fabricated by blending the as-prepared fats with 1,3-distearoyl-2-oleoyl glycerol (SOS)-rich fats obtained by he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…(2021) Solvent (Hexane) PS showed lower diacylglycerols content. Hwang et al. (2021) Addition of limonene as green additive Solid fat content, crystallization temperature and cloud point of POl decreases.…”
Section: Fractionation Of Palm Oilmentioning
confidence: 99%
See 1 more Smart Citation
“…(2021) Solvent (Hexane) PS showed lower diacylglycerols content. Hwang et al. (2021) Addition of limonene as green additive Solid fat content, crystallization temperature and cloud point of POl decreases.…”
Section: Fractionation Of Palm Oilmentioning
confidence: 99%
“…(2018) fractionated PS with acetone and found that PS was made up of spherulites with massive rod-like crystals. Solvent fractionation has a high separation efficiency and increases the yield of the targeted phase ( Kyselka et al., 2018 ; Hwang et al., 2021 ). This serves as foundation for the development of baking margarine and pastry shortening ( Podchong et al., 2018 ).…”
Section: Fractionation Of Palm Oilmentioning
confidence: 99%
“…FFA and acylglycerols in the samples were identified by comparing their retention times (FFA,MAG,DAG,and TAG, with those of reference standards. The FFA, MAG, DAG, and TAG standards were prepared from raw BMO following the method described by Hwang et al (2021). Briefly, FFA and each acylglycerol species were obtained by pancreatic-lipase-catalyzed hydrolysis, followed by TLC separation, band scraping, and recovery using diethyl ether as the extraction solvent.…”
Section: Analysis Of Ffa and Acylglycerol Contentmentioning
confidence: 99%